Trend Fashion pada Sosial Media Instagram @enazirashf_ dalam Gaya Berpakaian Islami Mahasiswi Komunikasi dan Penyiaran Islam Angkatan 2019 Universitas Ibn Khaldun Bogor - Irfan Yanuar; Asep Gunawan; Noneng Siti Rosidah (KOLONI, 2023)
Fashion trends in Muslim clothing used by Muslim women in Indonesia are experiencing developments in line with the current of modernization. Various kinds of Muslim fashion models can be easily accessed through sophisticated technology. Students in the Department of Islamic Broadcasting Communication, Faculty of Islamic Studies, Ibn Khaldun University, Bogor, are equipped with good religious knowledge and are considered to be the younger generation, experiencing the progress of up-to-date Muslim women's fashion trends and there are changes in student behavior when wearing these clothes. The focus of this thesis discussion is on Islamic fashion trends on the Instagram account @enazirashf_ in Islamic clothing styles among female students majoring in Islamic Broadcasting Communication, Faculty of Islamic Religion, Ibn Khaldun University, Bogor, especially the class of 2019. This research aims to find out fashion trends on Instagram social media @enazirashf_ and find out fashion trends on social media Instagram @enazirashf_ in the clothing styles of Islamic Communication and Broadcasting students class of 2019 at Ibn Khaldun University. Research data was obtained using qualitative methods with descriptive analysis. The data collection techniques used are through observation, interviews and documentation. The results of this research show that the fashion trends that exist on the Instagram account @enazirashf_ are the use of Islamic Muslim clothing, gamis, casual and abaya, and students majoring in Islamic Broadcasting Communication, Faculty of Islamic Studies have implemented the Muslim clothing fashion trends that exist on the Instagram account @enazirashf_ These have value in terms of faith, health and worship.